Myo‐inositol enhances drought tolerance in creeping bentgrass through alteration of osmotic adjustment, photosynthesis, and antioxidant defense. Issue 4 (2nd June 2020) - Li, Zhou; Fu, Jingyan; Shi, Diwen; Peng, Yan
Abstract: Myo‐inositol (MI) regulates stress adaptation in plants. The objective of this study was to investigate effects of foliar MI application on improving drought tolerance associated with osmotic adjustment (OA), photosynthesis, and antioxidant defense in creeping bentgrass ( Agrostis stolonifera L.). Both MI‐pretreated (1 mM) and untreated plants were subjected to drought stress or well‐watered conditions for 12 d in growth chambers. Results showed that exogenous MI application protected plants from drought damage by improving OA and water use efficiency, and this contributed to better water status in creeping bentgrass. Interestingly, the foliar spray of MI promoted the accumulation of water‐soluble carbohydrates but decreased drought‐induced free proline in leaves. The MI‐pretreated plants exhibited significantly greater chlorophyll (Chl) content, photochemical efficiency (Fv/Fm), performance index on an absorption basis (PIABS), and net photosynthetic rate (Pn) than untreated plants in response to drought stress. Foliar application of MI decreased superoxide anion radical, H2 O2, and malondialdehyde contents and electrolyte leakage but increased superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) activities and gene expression in leaves under drought stress. This study indicates that MI‐induced drought tolerance was involved in the maintenance of better water relation associated with increases in OA and water use efficiency, the decline in Chl loss for photosynthetic maintenance, and improvement in antioxidant enzymes activity and gene expression contributing to less oxidative damage under drought stress. It is worth further investigating stress‐defensive proteins and metabolites induced by MI in turfgrass or other plant species under drought stress or other abiotic stresses.